Where is the best position to place a dosemeter in order to assess the eye lens dose when lead glasses are used?. (November 2017) - Silva, Edilaine Honorio da; Struelens, Lara; Covens, Peter; Ueno, Satoshi; Ube, Michiko; Vanhavere, Filip; Buls, Nico
Abstract: The objective of this study was to evaluate the feasibility of assessing the eye lens dose when lead glasses are used, by attaching a small radiophotoluminescent (RPL) glass dosemeter to the lead glasses. RPL dosemeters were placed over and under the shielding of the glasses and their response was evaluated for a range of parameters, including irradiations in a standard X-ray beam and Monte Carlo simulations of a cardiac/radiologic intervention (scattered beam). For the specific situations taken into account in this study, the optimal position was found to be a dosemeter placed close to the bridge of the lead glasses, over its shielding. Highlights: The best position to place an eye lens dosemeter on lead glasses was evaluated. The optimal position found is over the lead glasses, close to its bridge. Single dosimetry, compared to double dosimetry, is enough to assess eye lens dose.